Actions of social participation, identity and emotions of Chilean students of a private university (Polis (Santiago), 2019)
Chile has a long history of mobilizations related to access to education, and in the last decade the Movimiento Estudiantil (ME) has acquired great notoriety, linking students from the public system or from universities belonging to the Consejo de Rectores (Council of Rectors) on whom research has focused mainly. The main objective of this study was to analyze the relationship between collective identity (IC), politicized identity (IP), emotions (E) and social participation actions (PS) in students of a private university. The study included 224 students from the Psychology degree program at a private Chilean university, aged between 19 and 33. The results identify greater PS actions in men, with high influence of positive and negative emotions in activating such actions. On the other hand, in students who perceive an IC, the emotions of hope, shame and helplessness mediate the actions of PS and in students with a high IP, only the emotion of shame mediates participation. The implications of these findings and the possibilities and limitations presented for university students to participate in the ME from a private university are discussed.
Keywords: Student movement; participation; emotions; collective identity; politicized identity; sociology